Vascular Risk Factors and Cognition in Multiple System Atrophy - Zhang, Lingyu; Hou, Yanbing; Cao, Bei; Wei, Qian-Qian; Ou, Ruwei; Liu, Kuncheng; Lin, Junyu; Yang, Tianmi; Xiao, Yi; Zhao, Bi; Shang, HuiFang (Frontiers in Neuroscience, 2021)
Objective: Vascular risk factors have been reported to be associated with cognitive impairment (CI) in the general population, but their role on CI in multiple system atrophy (MSA) is unclear. This study aimed to explore the relationship between vascular risk factors and CI in patients with MSA. Methods: The clinical data and vascular risk factors were collected. The Montreal Cognitive Assessment tool was used to test the cognitive function of patients with MSA. Binary logistic regression was used to analyze the correlation between vascular risk factors and CI. Results: A total of 658 patients with MSA with a mean disease duration of 2.55 ± 1.47 years were enrolled. In MSA patients, hypertension was recorded in 20.2%, diabetes mellitus in 10.3%, hyperlipidemia in 10.2%, smoking in 41.2%, drinking in 34.8%, and obesity in 9.6%. The prevalence of CI in patients with MSA, MSA with predominant parkinsonism (MSA-P), and MSA with predominant cerebellar ataxia (MSA-C) was 45.0%, 45.1%, and 44.9%, respectively. In the binary logistic regression model, patients with more than one vascular risk factors were significantly more likely to have CI in MSA (OR = 4.298, 95% CI 1.456–12.691, P = 0.008) and MSA-P (OR = 6.952, 95% CI 1.390–34.774, P = 0.018), after adjusting for age, sex, educational years, disease duration, and total Unified multiple system atrophy rating scale scores. Conclusion: Multiple vascular risk factors had a cumulative impact on CI in MSA. Therefore, the comprehensive management of vascular risk factors in MSA should not be neglected.